Neutralizing Effects of Mimosa pigra Stem-Bark against Selected Snake Venom from Malaysian Habitat - Afendi, Nor Safwan Nor; Saferi, Noor Syahila Ahamad; Badgujar, Vishal Bhagwan; Fazil, Nur Fatin Afiqah Mohd; Sami, Farheen; Badgujar, Sangita; Shah, Hameeth; Kumar, Arun; Majeed, Shahnaz; Ansari, Mohammed Tahir (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction: Mimosa pigra L. (M. pigra) regarded as significant undesirable weed in India, Africa, Australia, South-East Asia and some Pacific islands. Preliminary evidence of the use of the plants by rural community for medical purpose to cure snakebites. The purpose of this research was to validate the traditional claims and usefulness of M. pigra L. in the management of envenomation caused by various poisonous snakes found in Malaysia, such as the King Cobra, Malayan Pit Viper, Banded Krait and Cobra. Materials and Methods: The powdered stem bark of M. pigra L. was subjected to methanolic extraction and the resulting extract was examined for preliminary phytochemical screening. The in vitro snake venom neutralization effects of the extract were investigated using the Phospholipase Inhibition Activity (PIA), Venom Induced Hemolysis (VIH) and Adenosine Diphosphate (ADP) induced platelet aggregation methods. In addition, an impregnated disc containing the venom and the stem bark extract was tested to neutralize the lethality induced by the venom using an egg embryo model. Results: The in vitro assays PIA, VIH and ADP-induced platelet aggregation demonstrated that the methanolic extract of M. pigra L. bark exhibited dose dependent neutralization effects against snake venoms from King Cobra, Malayan Pit Viper, Banded Krait and Cobra. A significant neutralization effect was observed in PIA, VIH and ADP activity at a concentration of 640 µg/mL. The LD50 of the extract was determined to be 2.419 µg/µL. At an extract concentration of 30 µg/µL to 50 µg/µL, M. pigra L. extract was effective in countering the vulnerability of Ophiophagus Hannah (O. Hannah) snake venom. The SDS page revealed that the neutralization activity may be attributed to the arrest of the fibrinolytic activity of the cobra venom. Discussion: The study confirms that the methanolic extract of M. pigra L. stem bark. is effective in neutralizing snake venoms, both in vitro and in vivo using an egg embryo model. These findings validate the traditional claims regarding the use of M. pigra L. in the treatment of snakebites.
Keywords: Egg embryo model; Fibrinolytic; O. Hannah; M. pigra L; Phospholipase Inhibition; Activity; Snake venom